(untitled) (Third Sector Social Economic Review, 2023)
This study examines the use of social media by local foundations in Kastamonu. The foundations located in Kastamonu are listed on the official website of the General Directorate of Foundations, and a total of 39 foundations in the province were identified. When examining the social media accounts of these foundations, it is found that only three foundations are active on social media. The data from all social media platforms belonging to the three identified foundations is examined using document and content analysis methods. The data obtained from the social media accounts is first subjected to document analysis, which provides descriptive results. Then, the study applies content analysis by evaluating the posts of the social media accounts active between January 1, 2022, and December 31, 2022. The study shows that 92% of the foundations in Kastamonu are not present on social media. It is found that the foundations that have accounts on social media platforms only use Instagram, Facebook, and YouTube. It is noted that some of the foundations’ accounts on social media have not been shared for a long time, while others have been opened recently. Most of the accounts of the same foundation opened on different platforms do not have information and link buttons to other accounts on social media, so the ""connectivity"" function of social media has not been sufficiently used. Instagram is the most used platform by the foundations in Kastamonu. It was found that the foundations use the accounts on Instagram and Facebook mainly to ""promote the work of the foundation"" and the accounts on YouTube to ""promote important people connected to the foundation.""